Investigating English language anxiety among UiTM Sarawak undergraduates / Vicky Chin, Ting Hie Ling and Yeo Jiin Yih - Vicky, Chin; Ting, Hie Ling; Yeo, Jiin Yih (Universiti Teknologi MARA, Kedah, 2016)
Second or foreign language learning can be a demanding task for many language learners. One of the essential factors is the existence of anxiety. In relation to this, the present study aims to investigate the level of English language anxiety experienced by university students as well as to identify the factors that lead to such anxiety. The Foreign Language Classroom Anxiety Scale (FLCAS) which is developed by Horwitz et al. (1986) was administered to 149 first year Diploma students. Data analysis on the FLCAS items were analysed using SPSS 22. The findings revealed that majority of the students experienced a moderate level of English language anxiety with anxiety of English classes being the main factor which contributed to the respondents’ language learning anxiety, followed by fear of test, communication/ speech apprehension and finally fear of negative evaluation. The study also indicated that most of the students were unmotivated to attend English classes and unproductive in preparing language tests. Nevertheless, majority of the students perceived themselves as confident and not anxious when speaking with native English speakers. The findings from this study provide pedagogical implications to the English as second language (ESL) practitioners and could potentially assist instructors in alleviating debilitating anxiety which in turn can yield better learning outcomes.